A Study on Hover Performance of Ducted Fans for an Unmanned VTOL Aircraft. (25th July 2022) - Choi, Young Jae; Wie, Seong-Yong; Chae, Sanghyun
Abstract : In this study, ground tests and numerical analysis were performed to verify the hover performance of the second ducted fan model designed by this research team. Shape of the duct inner surface was asymmetric in longitudinal direction, and considering various aspects such as test site or costs for test operation, a 40% scaled-down model of the ducted fan was adopted for this study. Both the results of the tests and the analysis were found to be coherent, and it was verified that the ducted fan was verified to be well designed to achieve the targeted performance. Furthermore, the performance of this ducted fan was compared with that of the symmetric one to determine the effects of the difference in the duct shape on the performance. It was observed that the symmetric ducted fan performs better in hovering flight, although the asymmetric ducted fan was sufficiently satisfied with the design intention.